(untitled) - Henn, Matt (Los Angeles, 2009)
A Critical Introduction to Social Research is the new, updated, and improved edition of A Short Introduction to Social Research. This book introduces students and researchers to the key ideas and issues that inform research practice. In it, Matt Henn, Mark Weinstein and Nick Foard provide a clear and easy-to-understand route-map to help the reader plan their research project from beginning to end. This book is perfect for use on introductory methods courses and is also an invaluable guide for the first time researcher embarking on their own small-scale research project. The new Second Edition now features updated chapters which reflect recent debates and developments in the field.
Keywords: Social sciences,Khoa học Xã hội; Research,Nghiên cứu